Implementasi Kampus Mengajar Dua di UPT SPF SD Negeri 162 Ara Kabupaten Bulukumba Provinsi Sulawesi Selatan - Saman Saman (Pusat Riset dan Inovasi Nasional, 2022)
The method of implementing campus teaching activities refers to the implementation procedures that have been carried out stipulated by the Ministry of Education of the Republic of Indonesia. This procedure was obtained through provision carried out directly by the ministry of education. The debriefing activity was divided into two sessions, namely the first was debriefing for field supervisors (DPL) and the second was debriefing for students who had passed the selection. Campus Teaching Batch 2 is a continuation of the Campus Teaching Batch 1 program, part of the Independent Campus program which involves students at each campus from various educational backgrounds to help with the teaching and learning process in schools, especially at the elementary and middle school levels and provide opportunities for them to learn and develop yourself through activities outside the lecture class. While at UPT SPF SD Negeri 162 Ara, students planned and implemented several work programs, namely teaching in class (My Fairy Tales Today, Fun Calistung, Prokes Education (Health Protocols), Let's Get Creative, Let's Experiment, Back to Nature, Role Playing, Literacy Mading, English Class, World Time, Teaching and Learning, Introduction to technology tools (laptops), Training in creating technology-based learning media, such as learning videos and PPT, Introduction to learning applications (Zoom, Classroom, Google Meet, etc.), Helping with library bookkeeping administration, Helping in the administration of student dapodik and assisting with supervision during UAS.